Trifluoromethylcinnamanilide Michael Acceptors for Treatment of Resistant Bacterial Infections - Strharsky, Tomas; Pindjakova, Dominika; Kos, Jiri; Vrablova, Lucia; Smak, Pavel; Michnova, Hana; Gonec, Tomas; Hosek, Jan; Oravec, Michal; Jendrzejewska, Izabela; Cizek, Alois; Jampilek, Josef (International journal of molecular sciences, 2022)
A series of thirty-two anilides of 3-(trifluoromethyl)cinnamic acid (series 1) and 4-(trifluoromethyl)cinnamic acid (series 2) was prepared by microwave-assisted synthesis. All the compounds were tested against reference strains Staphylococcus aureus ATCC 29213 and Enterococcus faecalis ATCC 29212 and resistant clinical isolates of methicillin-resistant S. aureus (MRSA) and vancomycin-resistant E. faecalis (VRE). All the compounds were evaluated in vitro against Mycobacterium smegmatis ATCC 700084 and M. marinum CAMP 5644. (2E)-3-[3-(Trifluoromethyl)phenyl]-N-[4-(trifluoromethyl)phenyl]prop-2-enamide (1j), (2E)-N-(3,5-dichlorophenyl)-3-[3-(trifluoromethyl)phenyl]prop-2-enamide (1o) and (2E)-N-[3-(trifluoromethyl)phenyl]-3-[4-(trifluoromethyl)-phenyl]prop-2-enamide (2i), (2E)-N-[3,5-bis(trifluoromethyl)phenyl]-3-[4-(trifluoromethyl)phenyl]-prop-2-enamide (2p) showed antistaphylococcal (MICs/MBCs 0.15-5.57 μM) as well as anti-enterococcal (MICs/MBCs 2.34-44.5 μM) activity. The growth of M. marinum was strongly inhibited by compounds 1j and 2p in a MIC range from 0.29 to 2.34 μM, while all the agents of series 1 showed activity against M. smegnatis (MICs ranged from 9.36 to 51.7 μM). The performed docking study demonstrated the ability of the compounds to bind to the active site of the mycobacterial enzyme InhA. The compounds had a significant effect on the inhibition of bacterial respiration, as demonstrated by the MTT assay. The compounds showed not only bacteriostatic activity but also bactericidal activity. Preliminary in vitro cytotoxicity screening was assessed using the human monocytic leukemia cell line THP-1 and, except for compound 2p, all effective agents did show insignificant cytotoxic effect. Compound 2p is an interesting anti-invasive agent with dual (cytotoxic and antibacterial) activity, while compounds 1j and 1o are the most interesting purely antibacterial compounds within the prepared molecules.
Keywords: Cinnamates; Staphylococcal Infections; Microbial Sensitivity Tests; lidé; stafylokokové infekce; Methicillin-Resistant Staphylococcus aureus; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; cinnamáty; methicilin rezistentní Staphylococcus aureus; Humans